The Relationship between Subjective Wellbeing and Subjective Wellbeing Inequality: Taking Ordinality and Skewness Seriously - Arthur Grimes; Stephen P. Jenkins; Florencia Tranquilli (Institute of Labor Economics (IZA), 2020)
We argue that the relationship between individual satisfaction with life (SWL) and SWL inequality is more complex than described by leading earlier research such as Goff, Helliwell, and Mayraz (Economic Inquiry, 2018). Using inequality indices appropriate for ordinal data, our analysis using the World Values Survey reveals that skewness of the SWL distribution, not only inequality, matters for individual SWL outcomes; so too does whether we look upwards or downwards at the (skewed) distribution. Our results are consistent with there being negative (positive) externalities for an individual's SWL from seeing people who are low (high) in the SWL distribution.
Keywords: D31; D63; I31; 330; subjective wellbeing; ordinal data; inequality; skewness; WVS